Geotecnologias aplicadas à análise e delimitação de Área de Preservação Permanente (APP) de cursos d’água - Melo, Emanuelle Zordan de (2020)
The execution of environmental mappings has several technical limitations, in which the need to monitor very large areas, with complex or nonexistent access, becomes an obstacle and takes a long time to perform. The use of a more agile tool that can assist in the inspection process and in the application of current environmental legislation can reduce the length of conventionally applied methods. In this sense, tools that can support such environmental analysis, such as remote sensing and the Geographic Information System - GIS, have been studied. These are technologies that enable quick and less costly mapping, as well as prospects about past, present and future scenarios of the use and conservation of natural resources. In the conservation scenario, Permanent Preservation Areas (PPAs) can be highlighted, which include environments of significant ecological relevance, covered or not by native vegetation, which act in the preservation of water resources, landscape, geological stability and biodiversity, further facilitating the gene flow. between fauna and flora and protecting the soil. These areas, although protected by law, can suffer anthropic impacts, thus requiring their proper delimitation and preservation. This research aimed to interpret the current legal guidelines regarding the approach and form of delimitation of hydrographic APPs, following the guidelines expressed in the State Forest Code (FC) (Law nº 20.922/2013), presenting a methodological proposal that enables and automates the process. delineation of these areas, from the application of the processes in a stretch of the Uberabinha River (Uberlândia/MG). For that, we used images obtained through an Unmanned Aerial Vehicle (UAV) and digital image processing techniques, manipulated in GIS environment. The application of the proposed methodology ensures the correct demarcation of the areas, eliminating the subjectivities existing in the regulatory legislations, which allow doubts in the understanding of the true limits and forms of delimitation of the protected areas. It is concluded that the research contributed to the reduction of subjectivity, costs and time spent in the processes of inspection, mapping and environmental analysis, helping in the correct interpretation of the current legal guidelines, ensuring the preservation of the environment and associated natural resources.